2019
DOI: 10.1007/s10555-019-09782-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging tumor acidosis: a survey of the available techniques for mapping in vivo tumor pH

Abstract: Cancer cells are characterized by a metabolic shift in cellular energy production, orchestrated by the transcription factor HIF-1α, from mitochondrial oxidative phosphorylation to increased glycolysis, regardless of oxygen availability (Warburg effect). The constitutive upregulation of glycolysis leads to an overproduction of acidic metabolic products, resulting in enhanced acidification of the extracellular pH (pHe~6.5), which is a salient feature of the tumor microenvironment. Despite the importance of pH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 163 publications
1
115
0
2
Order By: Relevance
“…Indirect measurements of acidic regions in the TME have been obtained in canine OS samples by immunohistochemistry (IHC) analysis (Avnet et al , 2017). Consequently, non‐invasive imaging approaches are needed to provide accurate in vivo measurements of tumor acidosis (Anemone et al , 2019; Consolino et al , 2020). Previous MRS approaches reported intratumoral acidosis in murine fibrosarcoma models, but lacked the ability to assess the spatial distribution (Vaupel et al , 1989, 1994).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect measurements of acidic regions in the TME have been obtained in canine OS samples by immunohistochemistry (IHC) analysis (Avnet et al , 2017). Consequently, non‐invasive imaging approaches are needed to provide accurate in vivo measurements of tumor acidosis (Anemone et al , 2019; Consolino et al , 2020). Previous MRS approaches reported intratumoral acidosis in murine fibrosarcoma models, but lacked the ability to assess the spatial distribution (Vaupel et al , 1989, 1994).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…Previous MRS approaches reported intratumoral acidosis in murine fibrosarcoma models, but lacked the ability to assess the spatial distribution (Vaupel et al , 1989, 1994). Recently, a novel MRI‐based approach has been proposed for in vivo imaging of extracellular tumor pH with high accuracy and spatial resolution by exploiting iopamidol, an FDA‐approved X‐ray contrast medium that allows potential clinical translation (Longo et al , 2014; Anemone et al , 2019). Preclinical studies have shown the capability of this pH mapping method to assess the correlation between dysregulated glycolysis and tumor acidosis (Longo et al , 2016) and monitor the treatment response to anticancer therapies targeting glycolysis (Anemone et al , 2017).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…De par leur insertion pH-dépendante au sein des membranes cellulaires (pH<6,5), les peptides pHLIP (pH-low insertion peptides) assurent la détection des zones acides des tumeurs de souris par tomographie à émission de positrons ( Figure 2). En clinique, l'imagerie IRM de transfert d'aimantation par échange chimique avec le iopamidol (Acido-CEST pour acido-chemical exchange saturation transfer) permet la détection de l'acidification de tumeurs de l'ovaire et du sein [11].…”
Section: Sélection D'anticorps Ph-dépendants Par Phage Displayunclassified
“…In the clinical setting, positron-emission tomography (PET) technique is routinely exploited for measuring glucose uptake via 18F-fluorodeoxyglucose (FDG) injection, although radiation exposure limits repeated longitudinal studies (14)(15)(16). Furthermore, magnetic resonance imaging (MRI) offers a wide panel of approaches, by combining an optimal tissue contrast and good spatial information with acceptable sensitivity, to quantitatively interrogate several aspects of tumor microenvironment, including tumor metabolism and acidosis (17)(18)(19)(20). One of the most promising and emerging technique for investigating tumor metabolism is the chemical exchange saturation transfer (CEST)-MRI (21,22).…”
Section: Introductionmentioning
confidence: 99%